Effect of fourteen days of acclimatization on athletic performance in tropical climate - Voltaire, B.; Galy, O.; Coste, O.; Racinais, S.; Callis, A.; Blonc, St.; Hertogh, C.; Hue, O. (Canadian Journal of Applied Physiology, 2002)
In order to study the acclimatization process over 14 days of exposure to tropical climate, 9 triathletes performed 4 outdoor indirect continuous multistage tests in both thermoneutral and tropical conditions. The thermoneutral test (TN, 14 ¡C, 45% rh) was performed before traveling to the tropical area (Martinique, FWI). The tropical tests were performed 2, 8, and 14 days after arrival (32.9 ¡C, 78% rh). During each trial, we measured tympanic temperature, sweat rate, body mass loss, heart rate (HR), and performance. The results showed that 1) the mean tympanic temperature was greater in T2 (P < .001), T8 (P < .01) and T14 (P < .01) than in TN and significantly lower in T14 than in T2 (P < .05); 2) the mean sweat rate was significantly greater (P < .001) in T2, T8 and T14 than in TN and significantly greater (P < .05) in T8 and T14 than in T2; 3) the body mass loss after trials was significantly greater (P < .001) in T2, T8 and T14 than in TN and significantly greater (P < .05) in T8 and T14 than in T2; 4) the mean HR and HR at rest were significantly higher (P < .005) in T2 than in TN, T8, T14 and the mean HR was significantly lower (P < .05) in T14 than in the other trials; and 5) the performance time was significantly lower in T2 (P < 0.02), T8 (P < 0.03) and T14 (P < 0.05) than in TN. We concluded that 14 days of exposure to tropical climate led to changes in physiological parameters but were still insufficient to ensure complete acclimatization in well-trained athletes. The hot/wet climate induced impairment of physiological responses and performance that were still evident on the 14th day.